Hsa-miR-142-3p reduces collagen I in human scleral fibroblasts by targeting TGF-β1 in high myopia. (June 2022) - Li, Qinglan; Zheng, Qianyun; He, Jianfeng; Li, Ling; Xie, Xiangyong; Liang, Hao
Abstract: High myopia has been continually increasing globally until now and often results in visual impairment. Scleral extracellular matrix (ECM) remodeling is considered a common factor contributing to progression of myopia. However, the role of microRNAs (miRNAs) in regulating scleral ECM organization is not well understood. We aimed to explore the effect and regulatory mechanism of hsa-miR-142-3p on collagen I in human scleral fibroblasts in high myopia. First, next-generation sequencing was conducted to identify 37 miRNAs differentially expressed in the aqueous humor of high myopia samples and control samples. Furthermore, hsa-miR-142-3p in the aqueous humor was found to positively relate to the ocular axial length. Besides, the results of immunofluorescence and Western blot assay indicated that hsa-miR-142-3p overexpression decreased collagen I expression in the human fetal scleral fibroblasts (HFSFs); while hsa-miR-142-3p downregulation increased collagen I. Moreover, hsa-miR-142-3p targets TGFβ-1 gene expression. Quantitative polymerase chain reaction (qPCR) and Western blot analysis showed that miRNA 142-3p reduced TGFβ-1 expression while an inhibitor had an opposite effect. Therefore, there is an inverse relationship between changes in miR-142-3p expression levels and those of collagen1a1 in human scleral fibroblasts. Such a dependence suggests that miR-142-3p may be a target to improve therapeutic management of this condition. Highlights: miRNAs expression profile in high myopia was detected by next-generation sequencing. Hsa-miR-142-3p is positively associated with the ocular axial length. Hsa-miR-142-3p decreases collagen I in HFSFs. Hsa-miR-142-3p targets TGF-β1 in HFSFs.